MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENANAMKAN NILAI-NILAI MODERASI BERAGAMA PADA SMKN 1 TAMIANG LAYANG KABUPATEN BARITO TIMUR - Azimi, Bahrul; Susanto, Didi; Yuliansyah, Muhammad (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The research aims to (1) Describe the strategies implemented by the school principal in instilling the values of religious moderation at SMKN 1 Tamiang Layang, East Barito Regency (2) Describe the perceptions of teachers and students regarding the values of religious moderation applied by the principal at SMKN 1 Tamiang Layang Regency. East Barito (3) Describe the challenges faced by school principals in implementing the values of religious moderation at SMKN 1 Tamiang Layang, East Barito Regency. Qualitative descriptive research method, with data collection techniques in the form of observation, interviews, documentation. Data analysis techniques by validating data, organizing data and information, presenting findings and interpreting findings or making conclusions. Data validity testing is carried out by increasing persistence in research, triangulation, discussions with colleagues and member checking.The results of research on the strategy implemented by the school principal in instilling the values of religious moderation at SMKN 1 Tamiang Layang, East Barito Regency are planning by identifying needs through a survey of teachers' and students' understanding of the value of religious moderation, organizing by dividing tasks through meetings, creating an organizational structure and task description, Implementation by instilling five points, namely including moderation values in the school's vision and mission, integrating moderation principles in school culture, integrating moderation values in the curriculum, conducting training for teachers and collaborating with various related parties. The perception of teachers and students regarding the values of religious moderation implemented by the principal at SMKN 1 Tamiang Layang, East Barito Regency is that overall the value of religious moderation has been implemented by the principal through an approach to religion that emphasizes tolerance, mutual respect for differences, inviting joint activities, understanding that religion teaches the values of goodness and peace. The values of religious moderation that are implemented are group worship, providing facilities for every religious follower and celebrating religious holidays. The challenges faced by school principals in implementing the values of religious moderation at SMKN 1 Tamiang Layang, East Barito Regency are the diversity of cultures and beliefs, namely how to manage diversity so that conflicts or problems do not occur, the lack of understanding by teachers and students about the meaning of religious moderation and the politicization of religion which influences whether someone likes it or not.Keywords: Principal Leadership Management, Religious Moderation ValuesPenelitian bertujuan (1) Mendeskripsikan strategi yang diterapkan kepala sekolah dalam menanamkan nilai-nilai moderasi beragama pada SMKN 1 Tamiang Layang Kabupaten Barito Timur (2) Mendeskripsikan persepsi guru dan siswa mengenai nilai-nilai moderasi beragama yang diterapkan kepala sekolah pada SMKN 1 Tamiang Layang Kabupaten Barito Timur (3) Mendeskripsikan tantangan yang dihadapi oleh kepala sekolah dalam menerapkan nilai-nilai moderasi beragama pada SMKN 1 Tamiang Layang Kabupaten Barito Timur. Metode penelitian deskriptif kualitatif, dengan teknik pengumpulan data yaitu berupa observasi, wawancara, dokumentasi. Teknik Analisis data dengan memvalidasi data, mengorganisasi data dan informasi, menyajikan temuan dan penafsiran temuan atau membuat kesimpulan. Uji keabsahan data dilakukan dengan peningkatan ketekunan dalam penelitian, triangulasi, diskusi dengan teman sejawat dan membercheck.Hasil penelitian strategi yang diterapkan kepala sekolah dalam menanamkan nilai-nilai moderasi beragama pada SMKN 1 Tamiang Layang Kabupaten Barito Timur adalah perencanaan dengan melakukan identifikasi kebutuhan melalui survei pemahaman guru dan siswa tentang nilai moderasi beragama, pengorganisasian dilakukan membagi tugas melalui rapat, membuat struktur organisasi dan penjabaran tugas, Pelaksanaan dengan menanamkan lima poin yaitu memasukan nilai moderasi dalam visi misi sekolah, mengintegrasikan prinsip moderasi dalam budaya sekolah, mengintegrasikan nilai moderasi dalam kurikulum, melakukan pelatihan bagi guru dan bekerjasama dengan berbagai pihak terkait. Persepsi guru dan siswa mengenai nilai-nilai moderasi beragama yang diterapkan kepala sekolah pada SMKN 1 Tamiang Layang Kabupaten Barito Timur yaitu bahwa secara keseluruhan nilai moderasi beragama telah diterapkan kepala sekolah melalui pendekatan dalam beragama menekankan sikap toleransi, saling menghormati perbedaan, mengajak kegiatan bersama, memahami bahwa agama mengajarkan nilai-nilai kebaikan dan kedamaian. Nilai-nilai moderasi beragama yang diimplementasikan adalah ibadah bersama, memberikan fasilitas pada setiap pemeluk agama dan merayakan hari besar keagamaan.Tantangan yang dihadapi oleh kepala sekolah dalam menerapkan nilai-nilai moderasi beragama pada SMKN 1 Tamiang Layang Kabupaten Barito Timur adalah keragaman budaya dan keyakinan yakni cara mengelola keragaman agar tidak terjadi konflik atau permasalahan, minimnya pemahaman guru dan siswa tentang makna moderasi beragama dan adanya politisasi agama yang menjadi pengaruh terhadap suka dan tidaknya terhadap seseorang.Kata Kunci : Manajemen Kepemimpinan Kepala Sekolah, Nilai Moderasi Beragama